Integrasi Spiritualitas dan Rasionalitas: Pendekatan Studi Literature Review atas Relasi Ilmu Keagamaan dan Sains - Haikal, Faza; Sicha, Ainus (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2025)
The separation between religious knowledge and science has long created the impression that spirituality is unrelated to rationality, thus hampering efforts to provide a comprehensive scientific understanding. This study examines this issue from a contemporary educational perspective, emphasizing the urgency of collaboration between divine values and scientific approaches in shaping intellectual intelligence that aligns with students' noble character. The main objective of this study is to examine the possibility of a harmonious relationship between spiritual aspects and scientific reasoning in learning, while also testing the idea that integrating the two can create a more humanistic and meaningful educational process. This study was conducted using qualitative methods based on literature studies using thematic analysis of various scientific references, educational regulations, and theories of Islamic epistemology and modern science. Data were analyzed through categories related to integrated curriculum models, strengthening morals, and the ethical basis for developing scientific knowledge. The research findings show that integrating religious dimensions into science learning can increase ethical awareness, guide the wise application of knowledge, and balance cognitive aspects with students' spirituality. The implications of this research point to the need for curriculum reform and pedagogical approaches that integrate faith and reason in educational institutions, particularly in Muslim-majority environments. This study concludes that the unity of knowledge approach contributes to building a generation that is intellectually superior, ethical, and adaptive to global developments, and encourages further research related to the application of integrative learning models in real contexts.